This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let f ( x ) = 2 − 3 x (ie the left-hand side of the given equation).
We see that f ( 0 ) = 1 and f ( 1 ) = 2 1 ; so the root must lie in this interval.
Let x 0 = 2 1 and x n + 1 = f ( x n ) .
Iterating, we find
n | x n |
0 | 0 . 5 |
1 | 0 . 5 7 6 8 … |
2 | 0 . 5 6 1 5 … |
3 | 0 . 5 6 4 … |
4 | 0 . 5 6 3 … |
5 | 0 . 5 6 4 … |
6 | 0 . 5 6 4 … |
so the root is 0 . 5 6 4 .
The more rigorous version of this is that the form given in the problem leads to a convergent iterated function system (IFS).
It's easy to check that f ′ ( x ) is negative, so there is a unique root. As above, it lies in the interval 0 < x < 1 . The condition for convergence of an IFS to a root x = a is that ∣ f ′ ( a ) ∣ < 1 ; this is also easy to verify. Since f ( x ) is pretty well-behaved, any starting value x 0 will work.
Problem Loading...
Note Loading...
Set Loading...
Given that ( 2 1 ) x 3 1 = x , ⟹ − x 3 1 ln 2 = ln x or ln x + x 3 1 ln 2 .
Let f ( x ) = ln x + x 3 1 ln 2 . By Newton-Raphton method , we have:
x n + 1 = x n − f ′ ( x n ) f ( x n ) = x n − x n 1 + 3 x 3 2 ln 2 ln x + x 3 1 ln 2
Assuming x 0 = 1 and using an Excel spreadsheet to implement, we have:
where the columns from left to right are x n , f ( x n ) , f ′ ( x n ) , and x n + 1 . Therefore x ≈ 0 . 5 6 4 .